Studies in law, politics, and society - Sarat, Austin (Studies in law, politics, and society ;, 2017)
Studies in Law, Politics, and Society provides a vehicle for the publication of scholarly articles within the broad parameters of interdisciplinary legal scholarship. In this latest edition of this highly successful research series, articles examine a diverse range of legal issues and their impact on and intersections with society. Topics covered: marriage equality and the demise of civil unions; the LGBTQ community in the 1980s; the landscape of choice regarding reproductive rights and vaccine refusal; the rights of unvaccinated children; a socio-legal framework for understanding the social control of pleasure; and a data re-use and its impact on group identity. This volume brings together leading scholars and will be vital reading for all those researching in this subject area.